Uranium-mediated electrocatalytic dihydrogen production from water - Halter, Dominik; Heinemann, Frank Wilhelm; Bachmann, Julien; Meyer, Karsten (Nature, 2016)
Depleted uranium is a mildly radioactive waste product that is stockpiled worldwide. The chemical reactivity of uranium complexes is well documented, including the stoichiometric activation of small molecules of biological and industrial interest such as H2O, CO2, CO, or N-2 (refs 1-11), but catalytic transformations with actinides remain underexplored in comparison to transition-metal catalysis(12-14). For reduction of water to H-2, complexes of low-valent uranium show the highest potential, but are known to react violently and uncontrollably forming stable bridging oxo or uranyl species(15). As a result, only a few oxidations of uranium with water have been reported so far; all stoichiometric(2,3,16,17). Catalytic H-2 production, however, requires the reductive recovery of the catalyst via a challenging cleavage of the uranium-bound oxygen-containing ligand. Here we report the electrocatalytic water reduction observed with a trisaryloxide U(iii) complex [(((ArO)-Ar-Ad,Me)(3)mes)U] (refs 18 and 19)-the first homogeneous uranium catalyst for H-2 production from H2O. The catalytic cycle involves rare terminal U(iv)-OH and U(v)= O complexes, which have been isolated, characterized, and proven to be integral parts of the catalytic mechanism. The recognition of uranium compounds as potentially useful catalysts suggests new applications for such light actinides. The development of uranium-based catalysts provides new perspectives on nuclear waste management strategies, by suggesting that mildly radioactive depleted uranium-an abundant waste product of the nuclear power industry-could be a valuable resource.